Assessment of the Kempe Family Stress Inventory in self-care post-restrain schizophrenia - Ah Yusuf; Muhammad Suhron; Rika Subarniati (Intelektual Pustaka Media Utama, 2019)
Basic Health Research stated that the prevalence of schizophrenia in the Indonesian population in 2018 showed schizophrenia was seven per mile; previously only 1.7 permil. The aim of the study was to explain the stress reaction and experience of families who have people with schizophrenia post-restrain. The Methods A total of 135 families who have people with schizophrenia post-restrain October to December 2018. This research was Mix Method employed Sequential Explanatory design. the research instrument used was The Kempe Family Stress Inventory (KFSI) and using in-depth interview. The results of the study illustrated that the total mean score of a stress reaction in families normal was 43.48 (S.D=5.6),mild was 34.33 (S.D=4.7) whilesevere was 56.45 (S.D=4.45). The psychological burden was expressed by families in the form of fear and worry. The results showed a reaction to high stress and family experience lacking in self-care of people with post-restrain mental disorders.